2012
DOI: 10.1134/s1023193512060158
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of electrolyte ions and water dissociation in anion-exchange membranes under intense current conditions

Abstract: Polarization characteristics of electromembrane systems (EMS) based on the Russian commer cial heterogeneous membranes MA 40 and MA 41, the anion exchange heterogeneous membrane AMH (Mega, Czech Republic), and the modified membrane MA 40M are studied by the method of rotating mem brane disk in dilute sodium chloride solutions. The effective transport numbers of ions are found; the partial voltammetric characteristics (VAC) with respect to chloride and hydroxyl ions are measured; the limiting cur rent densities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…In the case of NaCl (Figure 1), the shapes of the total and partial CVCs were close to those described in the literature [45,46] for strong electrolytes, which do not participate in the proton-exchange reactions. The experimental limiting current, which is determined by the tangent intersection method (Figure 1), was close to ilimLev.…”
Section: Resultssupporting
confidence: 85%
“…In the case of NaCl (Figure 1), the shapes of the total and partial CVCs were close to those described in the literature [45,46] for strong electrolytes, which do not participate in the proton-exchange reactions. The experimental limiting current, which is determined by the tangent intersection method (Figure 1), was close to ilimLev.…”
Section: Resultssupporting
confidence: 85%
“…pH decreases in the AWComp during acid whey deacidification were reported, in previous studies in DC current conditions [10,11], to be caused by the dissociation of lactic acid following lactate migration, and by protons generated from water splitting phenomenon appearing mainly, after a certain time, on the AEM diluate side, as observed by other authors on model salt solutions [22,23]. However, the results of the current study demonstrate that the application of an adjusted PEF ratio was efficient in the reduction of such pH variations.…”
Section: Resultsmentioning
confidence: 64%
“…The relevant data were shown in the left part of Table 4 (the simulated ED process). Table 4 indicated that both of glutamic acid and lysine were inclined to be adsorbed by cation-exchange membranes in the simulated ED process, which was reasonable concerning the fact that cation-exchange membranes usually have larger exchange capacities and higher stability than anion-exchange membranes [26]. However, the adsorption characteristics changed in the actual ED process.…”
Section: The Adsorption Of Amino Acids By Membranesmentioning
confidence: 92%